ANALISIS HIGHER ORDER THINKING SKILLS SISWA BERBANTUAN MEDIA PEMBELAJARAN AUGMENTED REALITY - Sylvia, Fitri; Ramdhan, Billyardi; Windyariani, Sistiana (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
This study aims to analyze the students’ higher order thinking skills with the aid of Augmented Reality as the learning media in one of the high school in Sukabumi regent. Higher order thinking skills are students’ abilities in processing and analyzing the problems then to find the best solutions in which students can restate based on their logical argumentations. The method used in study is a pre-experimental design. The research design used was a one-group pretest posttest design with purposive sampling technique. This was conducted to the XI graders in 2020/2021 academic year. The instrument used was multiple choice test. The result of the data analysis shows that Augmented Reality could train students’ higher order thinking skills seen from the improvement of the pretest and posttest of the study starting from the low category to good and very good category. It is concluded that the use of Augmented Reality as learning media can improve students’ higher order thinking skills and is useful for the continuity of teaching and learning processes focusing on learning outcomes.